2020
DOI: 10.1027/1015-5759/a000486
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Utility of a Short Form of the Pediatric Symptom Checklist-Youth Self-Report (PSC-17-Y)

Abstract: Abstract. The Pediatric Symptom Checklist-Youth self-report (PSC-Y) is a 35-item measure of adolescent psychosocial functioning that uses the same items as the original parent report version of the PSC. Since a briefer (17-item) version of the parent PSC has been validated, this paper explored whether a subset of items could be used to create a brief form of the PSC-Y. Data were collected on more than 19,000 youth who completed the PSC-Y online as a self-screen offered by Mental Health America. Exploratory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…However, item 13 showed a lower loading (0.127) than the remaining items. This finding is consistent with Bergmann et al [ 22 ], who validated the PSC-17-Y in English and reported a relatively low factor loading (0.233) for this item. Following the same logic as these authors, we maintained item 13 in the final set of items for the PSC-17-Y in Spanish, since it is important to keep the measure as simple as possible for respondents and clinicians to complete, score, and interpret and since the parent- and youth-reported short forms were identical except for this 1 item.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, item 13 showed a lower loading (0.127) than the remaining items. This finding is consistent with Bergmann et al [ 22 ], who validated the PSC-17-Y in English and reported a relatively low factor loading (0.233) for this item. Following the same logic as these authors, we maintained item 13 in the final set of items for the PSC-17-Y in Spanish, since it is important to keep the measure as simple as possible for respondents and clinicians to complete, score, and interpret and since the parent- and youth-reported short forms were identical except for this 1 item.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we hypothesized that the problem with this item could be the wording and that future studies might review it to improve the saturation in the factor. The PSC-17-Y also showed an invariant structure across both genders, again consistent with Bergman et al [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although the PSC-17-Y is not as extensively studied or validated as the PSC-17-P, there have been several studies reporting on the youth completed version of the tool, 22,28-31 some of which have promising validation statistics. 22,29,30 Approximately 1 out of 4 youth ages 10 to 16 years old had an identified risk factor during the 2 year study period. The majority of these adolescents were identified by a positive PSC-17-Y in at least 1 subscale or the total score.…”
Section: Screeningmentioning
confidence: 99%